JAMES JOYCE’S INFLUENCE ON CONTEMPORARY IRISH WRITERS - José Manuel Estévez-Saá (University of Bucharest Review. Literary and Cultural Studies Series, 2022)
Many of the most outstanding contemporary Irish writers have paid homage to James Joyce’s figure and work in their fiction. This paper examines the extent of Joyce’s influence on a selection of contemporary Irish writers both at a thematic and at an aesthetic level. It is my contention that their humanist reading of the Irish genius has only recently been paralleled by Joycean critics such as Declan Kiberd whose Ulysses and Us: The Art of Everyday Living (2009) recuperates the humanist writer that authors such as Edna O’Brien, William Trevor, Dermot Bolger or Joseph O’Connor have been vindicating in their works. Therefore, their appreciation of the Irish genius contrasts with mainstream critical focus on the aesthetic and technical virtuoso Joyce, more frequently perceived by Joycean scholars and by writers such as Samuel Beckett or Flann O’Brien. My work on the influence of Joyce’s work in the literary career of some of the most relevant contemporary Irish writers is also a revision of the general tendency among Joycean critics who have traditionally centered their efforts on tracing the impact of his work on European and English authors (Virginia Woolf, Gertrude Stein, Philip Roth, John Barthes, Salman Rushdie, etc.).